IceCube search for dark matter annihilation in nearby galaxies and galaxy clusters - Aartsen, M.; Abbasi, R.; Abdou, Y.; Ackermann, M.; Adams, J.; Aguilar, J.; Ahlers, M.; Altmann, D.; Auffenberg, J.; Bai, X.; Baker, M.; Barwick, S.; et al. (2013)
We present the results of a first search for self-annihilating dark matter in nearby galaxies and galaxy clusters using a sample of high-energy neutrinos acquired in 339.8 days of live time during 2009/10 with the IceCube neutrino observatory in its 59-string configuration. The targets of interest include the Virgo and Coma galaxy clusters, the Andromeda galaxy, and several dwarf galaxies. We obtain upper limits on the cross section as a function of the weakly interacting massive particle mass between 300 GeV and 100 TeV for the annihilation into bb¯, W+W−, τ+τ−, μ+μ−, and νν¯. A limit derived for the Virgo cluster, when assuming a large effect from subhalos, challenges the weakly interacting massive particle interpretation of a recently observed GeV positron excess in cosmic rays.